ANALISIS SPASIAL TEMPORAL ALIH FUNGSI LAHAN PERTANIAN (SAWAH) KE NON PERTANIAN TAHUN 2012-2021 DI KECAMATAN WIDODAREN, KABUPATEN NGAWI - Aufa Arifana Faisal; Yuli Priyana; Danardono Danardono; Taryono Taryono; Rudiyanto Rudiyanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Widodaren district has an area that is mostly still in the form of agricultural land. However, at this time, it has undergone a land function change, so it has an impact on the productivity of food crops. The purpose of this study was to analyze the function transfer of agricultural land (paddy fields) to non-agricultural land spatially temporally from 2012-2021. The method used was a secondary data analysis method accompanied by field observations. The results showed that in the period 2012-2021 the area of land conversion reached 1,226 ha . The transfer of land functions occurred from rice fields to settlements covering an area of 422.29 hectares, rice fields to mixed gardens covering an area of 477.62 ha, and rice fields to fields covering an area of 326.09 ha. Land conversion occurred in all villages in Widodaren District, namely in Banyubiru, Gendingan, Karangbanyu, Kauman, Kayutrejo, Kedunggudel, Sekaralas, Sekarputih, Sidolaju, Sidomakmur, Walikukun, and Widodaren villages.